A composite cathode membrane with CoFe2O4–rGO/PVDF on carbon fiber cloth: synthesis and performance in a photocatalysis-assisted MFC-MBR system. Issue 2 (8th December 2016) - Li, Yihua; Sun, Jiaqi; Liu, Lifen; Yang, Fenglin
Abstract : In this study, a photocatalytic composite membrane (PCM) coated with CoFe2 O4 (–rGO) and polyvinylidene fluoride (PVDF) on a carbon fiber cloth was firstly prepared by inclusion of nanoparticles in a PVDF casting solution. Abstract : In this study, a photocatalytic composite membrane (PCM) coated with CoFe2 O4 (–rGO) and polyvinylidene fluoride (PVDF) on a carbon fiber cloth was firstly prepared by inclusion of nanoparticles in a PVDF casting solution. The PCM with CoFe2 O4 (–rGO) functioned as the cathode membrane in a photocatalysis-assisted MFC-MBR system. Comparison tests with four types of MFe2 O4 photo-catalysts (M = Ni, Fe, Co, Zn) in PCM indicated that CoFe2 O4 had the highest oxygen reduction reaction (ORR) activity. Upon compositing with reduced graphene oxide (rGO), the CoFe2 O4 –rGO greatly improved the catalytic activity. Photocatalysis in the cathode greatly promoted both power generation and contaminant removal. The maximum power density of 942 mW m −3 ( versus anode volume) was achieved using this PCM with CoFe2 O4 –rGO, under visible-light irradiation, and the removal of tetracycline hydrochloride antibiotics in a photocatalysis-assisted MFC-MBR system was higher than that without irradiation. By efficiently decomposing recalcitrant substances, the photocatalysis-assisted MFC-MBR system exhibits better and broader application potential in wastewater treatment than a conventional MFC-MBR system. The beneficial effects of nanoparticles on flux and conductivity in the PVDF casting solution were also evaluated.